First-year college students' alcohol and hookup behaviours: sexual scripting and implications for sexual health promotion. Issue 1 (2nd January 2021) - Thorpe, Shemeka; Tanner, Amanda E.; Kugler, Kari C.; Chambers, Brittany D.; Ma, Alice; Jenkins Hall, Wendasha; Ware, Samuella; Milroy, Jeffrey J.; Wyrick, David L.
Abstract: This study used a sexual scripting framework to analyse data from the Online College Social Life Survey to examine the role of individual, (e.g. gender, race and alcohol use), relational (partner type, condom use behaviours), and contextual factors (sex ratios and fraternity/sorority affiliation) influencing 4, 292 first-year college students' hookup experiences. Results suggest that hookups are relatively "safe", with the the majority involving non-penetrative sexual behaviour, condom use, and familiar partners. However, alcohol use affected hookup behaviours and lower levels of condom use were associated with heavy alcohol use, even with less well known partners. Findings point to the importance of interventions that reinforce first-year students' positive behaviours and present them with protective behavioural strategies to use in the context of alcohol, and with repeat or well-known partners to reduce risk and have enjoyable, consensual sexual experiences.